Analisis Wacana Kritis Upaya Privatisasi dan Komersialisasi Mata Air dalam Surat Permohonan Izin Pengusahaan Air - Yusup Irawan; Hestiyana Hestiyana (Balai Bahasa Provinsi Bali, 2022)
This qualitative study aims to describe linguistic signs and reveal the ideology contained in CV. STB’letter for water exploitation to policy makers in West Bandung Regency. This research uses Halliday’s (1995) transitivity analysis and Fairclough's (1995) critical discourse analysis. At the linguistic analysis, it was identified that the material process transivity is most often used by CV. STB for positive imaging. At the interpretation analysis, it was identified that CV. STB as the applicant for water exploitation (1) claiming to have the obligation to exploit water which is marked by the relasional verb process, (2) self-image with a social spirit which is marked by the material verb process, and (3) self-image as a humble applicant with linguistic signs of mental processes. At the explanation stage, it was revealed that CV. STB has the ideology that (1) the water resources in the soil itself are privately owned, (2) the water concession permit will be issued if CV. STB makes